Heterostructures Regulating Lithium Polysulfides for Advanced Lithium‐Sulfur Batteries - Wang, Tao; He, Jiarui; Zhu, Zhi; Cheng, Xin‐Bing; Zhu, Jian; Lu, Bingan; Wu, Yuping (Advanced materials (Weinheim), 2023)
Sluggish reaction kinetics and severe shuttling effect of lithium polysulfides seriously hinder the development of lithium‐sulfur batteries. Heterostructures, due to unique properties, have congenital advantages that are difficult to be achieved by single‐component materials in regulating lithium polysulfides by efficient catalysis and strong adsorption to solve the problems of poor reaction kinetics and serious shuttling effect of lithium‐sulfur batteries. In this review, the principles of heterostructures expediting lithium polysulfides conversion and anchoring lithium polysulfides are detailedly analyzed, and the application of heterostructures as sulfur host, interlayer, and separator modifier to improve the performance of lithium‐sulfur batteries is systematically reviewed. Finally, the problems that need to be solved in the future study and application of heterostructures in lithium‐sulfur batteries are prospected. This review will provide a valuable reference for the development of heterostructures in advanced lithium‐sulfur batteries. Heterostructures could regulate lithium polysulfides by efficient catalysis and strong adsorption to solve the problems of poor reaction kinetics and serious shuttling effect of lithium‐sulfur batteries. This review systematically and detailedly analyzes the principle and the application of heterostructures as sulfur host, interlayer, and separator modifier to promote the performance of lithium‐sulfur batteries.